Cidades em disputa: gestão dos usos do espaço e política das práticas a partir da Praça Roosevelt, em São Paulo - Pimentel, André de Pieri (Universidade Federal de São Carlos, 2018)
This ressearch intents to analyse, based on ethnographic study made in Praça Franklin Roosevelt, a public square in the neighborhood of Consolação (Central region of São Paulo), interfaces between determined mechanisms of space management and their concrete appropriation, destabilization and resistences. Builded in 1970, in the middle of the brazilian military dictatorship, the square was completely rebuilded in the year 2010, by the cost of R$ 55 million. Among the intentions behind such intervention, there were an attempt to estabilish a higher state control of the uses of that space, considered as problematic from a urban planning point of view. But, despite the intense presence and transit of police forces in the space since the reconstruction, not only certain modalities of insurgent uses still occupy it but also many of them assume directly critical positions on that repressive management of the uses of public spaces. The focus on this ressearch is to think apropriations, questionings, ruptures, in an experience level, of political discourses and institutional mechanisms that act in the establishment of a restrictive and reppressive management.
Keywords: Política; Práticas; Ordenamento; Cotidiano; Estudos Urbanos; São Paulo; Praça Franklin Roosevelt; Politics; Practices; Management; Everyday life; Urban studies; São Paulo; Praça Franklin Roosevelt; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA